Synagogues in the works of Flavius Josephus : rhetoric, spatiality, and first-century Jewish institutions - Krause, Andrew R. (Ancient Judaism and Early Christianity, 2017)
In Synagogues in the Works of Flavius Josephus , Andrew Krause analyses the place of the synagogue within the cultural and spatial rhetoric of Flavius Josephus. Engaging with both rhetorical critical methods and critical spatial theories, Krause argues that in his later writings Josephus portrays the Jewish institutions as an important aspect of the post-Temple, pan-diasporic Judaism that he creates. Specifically, Josephus consistently treats the synagogue as a supra-local rallying point for the Jews throughout the world, in which the Jewish customs and Law may be practiced and disseminated following the loss of the Temple and the Land. Conversely, in his earliest extant work, Bellum judaicum , Josephus portrays synagogues as local temples in order to condemn the Jewish insurgents who violated them.